Socio-demographic predictors associated with capacity to engage in health care - Ran Sun; Linden Wu; Scott Barnett; Patsy Deyo; Ellen Swartwout (Patient Experience Journal, 2019)
Patient engagement is essential to improve outcomes and reduce healthcare costs. This study aimed to examine the socio-demographic factors associated with one’s capacity to engage in their health care. An observational, cross-sectional study was performed including patients from five medical/surgical units of four health systems. Patients’ engagement capacity was assessed using the person engagement index (PEI) instrument which contains four subscales: engagement in health care, technology use in health care, proactive approach to health care, and psychosocial support for health care. Separate general linear models were applied for the PEI total score and each of the four subscale scores. Our results show that younger age was associated with greater technology use in health care. Individuals with higher educational levels have a greater overall engagement and the use of technology in their health care. A higher level of psychosocial support was found among blacks and those being employed. No difference in the proactive approach was found by one’s socio-demographic factors. This study illustrated that an individual’s age, race, educational level, and employment status were associated with the capacity to engage in different aspects of health care activities. Providers need to assess one’s readiness for engagement to deliver customized interventions based on their needs and capacity to engage. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens